Transition metal carbides (MXenes) for efficient NiO-based inverted perovskite solar cells. (April 2021) - Saranin, D.; Pescetelli, S.; Pazniak, A.; Rossi, D.; Liedl, A.; Yakusheva, A.; Luchnikov, L.; Podgorny, D.; Gostischev, P.; Didenko, S.; Tameev, A.; Lizzit, D.; et al.
Abstract: In this work we demonstrate the beneficial role of MXene doping for both perovskite absorber and electron transporting layer in NiO-based inverted perovskite solar cells. The addition of MXenes permits on one side to easy tune the energy level alignment at perovskite/charge transporting layer interfaces, and on the other side to passivate traps states within the cell structure, which in turn improves charge extraction and collection at the electrodes. The MXene-based engineered cells showed superior performance, with power conversion efficiency exceeding 19% and improved stabilized power output with respect to reference devices. Due to the possibility to finely tune the MXene work function during their chemical synthesis and to their capability in modifying the optoelectronic properties of PSC layers when used as dopant, the proposed approach opens countless ways for engineering inverted PSC structure, strongly promising in term of long-term stability and future scalability on large area devices. Graphical Abstract: ga1 Highlights: MXenes are employed to engineer the inverted p-i-n perovskite solar cell (PSC) structure based on nickel-oxide hole transporting layer. Ti3 C2 Tx are exploited to modify the work function of p-i-n PSC constituting layers and their band alignments. MXenes addition into perovskite absorber and electron transporting layer improves efficiency up to 19.2% by hampering charge recombination. The WF tunability of MXenes is suggested as a general approach for boosting inverted PSC PCE over the current state of art.